Insulin-Like Growth Factor-1: A Promising Therapeutic Target for Peripheral Nerve Injury - Slavin, Benjamin R.; Sarhane, Karim A.; von Guionneau, Nicholas; Hanwright, Phillip J.; Qiu, Chenhu; Mao, Hai-Quan; Höke, Ahmet; Tuffaha, Sami H. (Frontiers in Bioengineering and Biotechnology, 2021)
Patients who sustain peripheral nerve injuries (PNI) are often left with debilitating sensory and motor loss. Presently, there is a lack of clinically available therapeutics that can be given as an adjunct to surgical repair to enhance the regenerative process. Insulin-like growth factor-1 (IGF-1) represents a promising therapeutic target to meet this need, given its well-described trophic and anti-apoptotic effects on neurons, Schwann cells (SC), and myocytes. Here, we review the literature regarding the therapeutic potential of IGF-1 in PNI. We appraised the literature for the various approaches of IGF-1 administration with the aim of identifying which are the most promising in offering a pathway towards clinical application. We also sought to determine the optimal dosage ranges for the various delivery approaches that have been investigated.